2009
DOI: 10.1007/s00125-009-1363-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of depressive symptoms in persons with diabetic peripheral neuropathy: a longitudinal study

Abstract: Aims/hypothesis The aim of the study was to determine whether diabetic peripheral neuropathy (DPN) is a risk factor for depressive symptoms and examine the potential mechanisms for this relationship. Methods This longitudinal study (9 and 18 month followup) of 338 DPN patients (mean age 61 years; 71% male; 73% type 2 diabetes) examined the temporal relationships between DPN severity (mean±SD; neuropathy disability score [NDS], 7.4±2.2; mean vibration perception threshold, 41.5±9.5 V), DPN somatic experiences (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
100
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(112 citation statements)
references
References 38 publications
(43 reference statements)
5
100
0
6
Order By: Relevance
“…Our previous work using standardised diagnostic criteria for neuropathy [18] demonstrated a significant association between DPN severity and increased depressive symptoms, but failed to demonstrate a relationship between past foot ulceration and either concurrent [19] or subsequent depression [20]. Consistent with our findings, recent data from a large population-based study of diabetes patients with past foot ulceration also found that these patients reported more symptoms of depression than patients without diabetes, but their level of depression symptoms did not differ from diabetes patients who had not had a foot ulcer [12].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Our previous work using standardised diagnostic criteria for neuropathy [18] demonstrated a significant association between DPN severity and increased depressive symptoms, but failed to demonstrate a relationship between past foot ulceration and either concurrent [19] or subsequent depression [20]. Consistent with our findings, recent data from a large population-based study of diabetes patients with past foot ulceration also found that these patients reported more symptoms of depression than patients without diabetes, but their level of depression symptoms did not differ from diabetes patients who had not had a foot ulcer [12].…”
Section: Introductionmentioning
confidence: 83%
“…However, it is unclear from the report whether analyses adequately controlled for potential confounding between neuropathy severity and depression; others using a larger population-based sample have failed to find this relationship [22]. As neuropathy, a well-established risk factor for foot ulceration [3], is also a risk factor for elevated depressive symptoms [19,20], this may be a major limitation of previous research.…”
Section: Introductionmentioning
confidence: 96%
“…A longitudinal study has shown that DSPN is a risk factor for depression and the strongest symptom associated with depression was unsteadiness. Pain with DSPN may also give rise to symptoms of anxiety (143). Two research tools that can be used to assess quality of life that are neuropathy specific are the NeuroQoL (Quality of Life in Neurological Disorders) (144) and QOL-DN (Norfolk Quality of Life-Diabetic Neuropathy) instruments (145).…”
Section: Psychosocial Factorsmentioning
confidence: 99%
“…Depression is an important comorbidity of DSPN [118][119][120][121]. Among neuropathic symptoms, it is pain and, primarily, postural instability (leading to gait uncertainty) that are associated with depression [119,120].…”
Section: Depressionmentioning
confidence: 99%
“…Among neuropathic symptoms, it is pain and, primarily, postural instability (leading to gait uncertainty) that are associated with depression [119,120]. In the same context, DSPN may be associated with poor quality of life [121], and painful symptoms may be linked with a reduced well-being index [122].…”
Section: Depressionmentioning
confidence: 99%